PARAMETER ANALYSIS AND COMPUTER SIMULATION OF SINE FILTERS IN VVVF-DRIVE - Mikhail Y. Pustovetov (Advanced Engineering Research, 2012)
The issues on the parameter determination of the sine filters for the VVVF-drive are considered. The computer simulation of the sine filter operation is resulted.